Evaluation of Two Cosmetic Products Formulated with Essential Oil Extracted from Copal Resin Obtained in Agroforestry Systems - Jorge Raymundo-Rodríguez; Julio César Buendía-Espinoza; Rosa María García-Núñez; Elisa del Carmen Martínez-Ochoa (Cosmetics)
Forest wealth, combined with innovative cosmetic applications, allows for the use of non-timber forest products like copal resin, diversifying resource use, promoting sustainable practices, preserving ecosystems, and generating income. The aim of this study was to evaluate a facial cream and a body gel formulated with essential oil extracted from copal resin obtained from agroforestry systems to determine their quality and consumer acceptance. Copal resin was collected from a silvopastoral system in Izúcar de Matamoros, Puebla, Mexico. Protocols were developed to ensure quality, safety, and efficacy, adhering to Mexican official standards, and accelerated stability tests were conducted to determine shelf life. Microbiological and irritability tests were performed to assess safety. Hedonic tests along with a random forest model were employed to identify the most important characteristics for consumer acceptance. The results indicated that both products met quality parameters regarding color, aroma, viscosity, and pH, and exhibited a shelf life of two years. Both products were free from harmful microorganisms, making them suitable for human application. Hydration, aroma, spreadability, and irritability were the most crucial variables for achieving higher consumer acceptance. Cosmetics can be formulated with copal resin essential oil.